HUBUNGAN PEMBERIAN NUTRISI DENGAN KEJADIAN REGURGITASI DI PMB BIDAN L KOTA BANDUNG - Gina Rismaliani; Maya Indriati; Naili Rahmawati (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
Regurgitation or spitting up is the backflow of stomach contents into esophagus, out through mouth and is not accompanied by contractions of the abdominal muscles. This research will be conducted using primary data and secondary data. This study entitled "The Relationship between Nutrition and Regurgitation" was conducted at PMB Bandung City with the primary data obtained. In this study, a cross-sectional research design was used using a quota sampling technique so that a total of 30 samples were obtained. it can be seen that the majority of respondents provided nutrition in the form of breast milk to their babies, namely as many as 15 people or 50%, 21 respondents (56.67%) experienced mild regurgitation. Based on the results fisher's exact test, it shows that p-value 0.048 0.05 or rejects H0. This shows that there is sufficient evidence to state that there is an effect between provision of nutrition and incidence of regurgitation at a significant level of α 5%. From 30 respondents, based on the incidence of regurgitation, it can be seen that majority of respondents provided nutrition in form of breast milk to their babies, namely as many as 15 people or 50%. While 9 respondents or 30% provided nutrition in the form of formula milk and 6 respondents (20%) provided combination nutrition between breast milk and formula milk. results of analysis using FiSher showed that there was sufficient evidence to state that there was an effect between the provision of nutrition and the incidence of regurgitation at a significant level of α 5%